The globalization of health care legal and ethical issues - Cohen, I. Glenn (Oxford ; New York : Oxford University Press, 2013)
'The Globalization of Health Care' offers a comprehensive legal and ethical analysis of the most interesting and broadest reaching development in health care of the last twenty years: its globalization.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Mar. 7, 2013).
Keywords: Medical care -- Law and legislation; Health services accessibility -- Law and legislation; Right to health -- Moral and ethical aspects; Health care reform; Medical ethics